The Use of Measuring While Drilling and Wireline Logging to Identify the Geological Strata in Qatar - Gravador-Villamor, Anna Grace; Pearce, Fay (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
In the field of engineering and construction in the Middle East, it is a common practice to economize a geotechnical investigation using a conventional scope, based on the lowest price. This tends to compromise the project integrity by either under- or over-designing the structure. However, a carefully considered ground investigation and engineering evaluation should be practiced in the early stages, to reduce the unknowns related to geology, ground strength and behavior, ultimately optimizing the geotechnical design, and project constructability and efficiency. This begs the question of whether ’cheap and conventional’ can ever equate to ’quality’ and what can be done to improve the geotechnical investigations. This paper focuses on ground investigations on rocks and presents the key advantages of utilizing instrumented drilling boreholes in combination with rotary coring boreholes, to collect accurate and good quality data on an accelerated schedule. The study identifies the bias of a conventional geotechnical investigation, highlighting how this can be reduced through the use of instrumented drilling and wireline logging, and how the data collected can define the typical trends observed in the Qatar stratigraphy through correlation from instrumented and rotary coring boreholes drilled in several locations across Qatar. The findings have significant implications on revolutionizing the current ground investigations in Qatar, providing a geotechnical investigation alternative that delivers more complete and high-quality data.